Osseous choristoma of the tongue: two case reports. (December 2016) - Adhikari, Bhoj; Sato, Jun; Morikawa, Tetsuro; Obara-Itoh, June; Utsunomiya, Masafumi; Harada, Fumiya; Chujo, Takatoshi; Takai, Rie; Yoshida, Koki; Nishimura, Michiko; Shakya, Mamata; Nagayasu, Hiroki; et al.
Abstract Background Osseous choristoma is a very rare, benign lesion in the maxillofacial region. It appears as a benign mass of normally matured bony tissue covered by the normal epithelium of the tongue. It is usually seen in front of the foramen cecum of the tongue. Surgical excision is the treatment of choice with an excellent prognosis and there have been very few cases of recurrence. Case presentation Here we present two cases of osseous choristoma on the dorsum of the tongue. Case 1 was a 15-year-old Japanese girl who presented with a painless but gradually growing swelling on the dorsum of her tongue approximately 1 year before her admission. Case 2 was a 21-year-old Japanese woman with a complaint of pain in the lower left, posterior side of her mouth. Histological findings showed that both lesions were composed of well-organized, mature, compact bone beneath the oral mucosal membrane. Subsequent to simple surgical excision, no recurrence of the lesions was observed after the follow-up period. Previous literatures have proposed both malformation and trauma hypotheses as the etiopathologies of osseous choristoma. However, the histopathological findings of the two cases in the present study do not support the trauma hypothesis. Conclusions Although osseous choristoma is clinically a benign condition, the underlying histopathological processes are important. The outcome of aberrant formation of calcified tissue in the vicinity of vital structures such as nerves and blood vessels may be of clinical significance.